Techniques for Estimating the Fiscal Costs and Risks of Long-Term Output-Based Payments - Boyle, Glenn; Irwin, Timothy (World Bank, Washington, DC, 2016)
Long-term commitments to make output-based payments for infrastructure can encourage private investors to provide socially valuable services. Making good decisions about such commitments is difficult, however, unless the government understands the fiscal costs and risks of possible commitments. Considering voucher schemes, shadow tolls, availability payments, and access, connection, and consumption subsidies, this paper considers measures of the fiscal risks of such commitments, including the excess-payment probability and cash-flow-at-risk. Then it illustrates techniques, based on modern finance theory, for valuing payment commitments by taking account of the timing of payments and their risk characteristics. Although the paper is inevitably mathematical, it focuses on practical applications and shows how the techniques can be implemented in spreadsheets.